In Vitro Release from Reverse Poloxamine/α‐Cyclodextrin Matrices: Modelling and Comparison of Dissolution Profiles. Issue 1 (8th November 2013) - Larrañeta, Eneko; Martínez‐Ohárriz, Cristina; Vélaz, Itziar; Zornoza, Arantza; Machín, Rubén; Isasi, José Ramón
<x xml:space="preserve">Abstract</x> Gels obtained by complexation of octablock star polyethylene oxide/polypropylene oxide copolymers (Tetronic 90R4) with α‐cyclodextrin (α‐CD) were evaluated as matrices for drug release. Both molecules are biocompatible so they can be potentially applied to drug delivery systems. Two different types of matrices of Tetronic 90R4 and α‐CD were evaluated: gels and tablets. These gels are capable to gelifying in situ and show sustained erosion kinetics in aqueous media. Tablets were prepared by freeze‐drying and comprising the gels. Using these two different matrices, the release of two model molecules, L‐tryptophan (Trp), and a protein, bovine serum albumin (BSA), was evaluated. The release profiles of these molecules from gels and tablets prove that they are suitable for sustained delivery. Mathematical models were applied to the release curves from tablets to elucidate the drug delivery mechanism. Good correlations were found for the fittings of the release curves to different equations. The results point that the release of Trp from different tablets is always governed by Fickian diffusion, whereas the release of BSA is governed by a combination of diffusion and tablet erosion. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:197–206, 2014